Persepsi Masyarakat Dayak Merap dan Punan tentang Pentingnya Hutan di Lansekap Hutan Tropis, Kabupaten Malinau, Kalimantan Timur - Lisnawati, Nining; Indawan, Andry; ., Sumardjo; Sheil, Douglas (Institut Pertanian Bogor (IPB University), 2004)
This study’s emphasis was on Dayak Merap and Punan people’s perception of the importance of forest. A participatory approach using scoring exercises was completed with seven forest-dwelling communities in the tropical landscape of Malinau, East Kalimantan. The findings suggest that unlogged forest was the most important land category for Dayak people. It provides for their livelihoods and well-being both directly and indirectly. ‘Forest’ has the heritage values and contains an abundance of valued and significant plants and animal. For the future, ‘forest’ is predicted to remain important for local people mainly for timber. Forests are exceptional in comparison with other land types in providing a wide range of highly valued goods and services, in most cases to a greater degree than other land types. In addition, the value of forests decreases less with apparent distances. However, logged forest is related as much less important, allowing us to consider improvements in forest management that might better protect local values.